2008
DOI: 10.1186/1476-4598-7-36
|View full text |Cite
|
Sign up to set email alerts
|

DNA repair gene ERCC2 polymorphisms and associations with breast and ovarian cancer risk

Abstract: Breast and ovarian cancers increased in the last decades. Except rare cases with a genetic predisposition and high penetrance, these pathologies are viewed as a polygenic disease. In this concept, association studies look for genetic variations such as polymorphisms in low penetrance genes, i.e. genes in interaction with environmental factors. DNA repair systems that protect the genome from deleterious endogenous and exogenous damages have been shown to have significantly reduced. In particular, enzymes of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(17 citation statements)
references
References 33 publications
(20 reference statements)
0
17
0
Order By: Relevance
“…Only a few studies have examined the role of SNPs in the NER pathway in both ovarian cancer risk and response to chemotherapy. [9][10][11][12][13][14] Those studies demonstrated that variants in the xeroderma pigmentosum (XP) complementation family group of proteins can predict platinum sensitivity and survival outcomes. 9,10 Because of the potential importance of the NER pathway, we sought to determine whether single-nucleotide polymorphisms in this pathway could be a prognostic marker of response to platinum-based chemotherapy in ovarian cancer.…”
mentioning
confidence: 99%
“…Only a few studies have examined the role of SNPs in the NER pathway in both ovarian cancer risk and response to chemotherapy. [9][10][11][12][13][14] Those studies demonstrated that variants in the xeroderma pigmentosum (XP) complementation family group of proteins can predict platinum sensitivity and survival outcomes. 9,10 Because of the potential importance of the NER pathway, we sought to determine whether single-nucleotide polymorphisms in this pathway could be a prognostic marker of response to platinum-based chemotherapy in ovarian cancer.…”
mentioning
confidence: 99%
“…It has a BRCA1 C-terminal domain (BRCT) which is characteristic of proteins involved in cycle checkpoint functions and DNA damage. XRCC1 [75,76], XRCC3, and XPD (ERCC2) [76][77][78] are involved in DNA repair. Polymorphisms in these genes are associated with increased breast cancer risk.…”
Section: Dna Repair Genementioning
confidence: 99%
“…NER operates in the presence of other enzymes, as the complex ERCC1 (excision repair cross-complementing group 1) and ERCC2 (excision repair cross-complementing group 2) [24,25]. ERCC2 gene product is associated with DNA unwinding when its product (protein XPD) is expressed [26]. XPD proteins act in the process as temporary helicase rolling out double helix to find DNA lesions caused by free radicals [27] with subsequent lesion removal [28].…”
Section: Introductionmentioning
confidence: 99%